Assessment of Serum Vitamin D Levels in Women with Polycystic Ovary Syndrome - Hamdi, Rana A.; Abdul-Qahar, Zina H.; Kadhum, Ekhlas J.; Alsaeed, Fatin A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Polycystic ovary syndrome (PCOS) is a common endocrinopathy in women of reproductive age with primary features of infertility, menstrual irregularity, and clinical or biochemical evidence of hyperandrogenism (hirsutism, acne and high androgen level). Vitamin D has a role in the development of metabolic and endocrine abnormalities in PCOS mediated by insulin resistance. Objective: Measure serum 25-hydroxy vitamin D levels in women with polycystic ovary syndrome and compare their levels with age and body mass index matched healthy controls. Also, assess the correlation between insulin resistance and 25-hydroxy vitamin D among women with PCOS. Subjects and Methods: Eighty eight women were involved in this study with age range (18-34 years). Subjects were divided into two groups: Group 1- forty five women with PCOS and Group 2- forty three women without PCOS (as controls). Serum 25-hydroxy vitamin D, insulin, free testosterone, Luteinizing hormone (LH), Follicle stimulating hormone (FSH) were measured by enzyme linked immunosorbent assay (ELISA), while serum calcium and fasting serum glucose were measured by spectrophotometer. Results: Significant increase in mean value of fasting serum glucose, insulin, homeostatic model assessment of insulin resistance (HOMA-IR), LH, LH/FSH ratio, and free testosterone with significant decrease in mean value of serum FSH, 25-hydroxy vitamin D, and calcium for patients with PCOS comparing to age and body mass index match controls. Additionally, significant negative correlations were found between serum 25-hydroxy vitamin D levels with fasting serum glucose (r= -0.484, p=0.01), fasting serum insulin (r= -0.422, p=0.04), and HOMA-IR (r= -0.542, p=0.0001) in women with PCOS. Conclusion: Vitamin D has a role in metabolic and hormonal disturbance seen in PCOS through impact of vitamin D on insulin releasing and function.